PENGEMBANGAN MULTIMEDIA INTERAKTIF PEMBELAJARAN TEKNIK MENGGAMBAR PROPORSI ILUSTRASI DESAIN TUBUH WANITA - Rita Nurjanah; Mila Karmila (Fesyen Perspektif, 2017)
Computer technology can support the learning process in the delivery of materials, methods and instructional media. In the learning process required media are able to attract the interest and motivation of learners in learning, one of them with interactive multimedia. This research aims to design and develop instructional media that are tailored to the needs of learners. Instructional media design illustration drawing techniques proportion of the female body is still conventional and this is the rationale for conducting research, interactive multimedia development will be an alternative to facilitate the learning process for students. The method used in this research is method of Research and Development (RD). Design and development of media made through the first phase, a preliminary study, examines the theory and analysis of learning activities. The second phase, to develop media with interactive multimedia. The third phase, to test or validate interactive multimedia instructional design illustration drawing techniques proportion of the female body. The results of the validation by subject matter experts to get the average value of a feasibility percentage of 98.9%, by multimedia specialists earn an average percentage of 90.6% viability and users get an average percentage of 92.7% viability. Based on the feasibility of the results of validation standard interactive multimedia learning drawing techniques proportions of a woman's body design illustrations included into the category of valid and fit for use.